Phytochemical, antioxidant activity and toxicity evaluation of medicinal plants commonly used for asthma management in Malawi - Mwambyale, Tuntufye (Kamuzu University of Health Sciences, 2022)
Asthma is a chronic disease characterized by recurrent attacks of breathlessness and wheezing, which vary in severity and frequency from person to person. There is minimal scientific research on the efficacy, doses, toxicity and safety of herbal remedies used in the management of asthma in many countries including Malawi. Therefore, this study determined the brief chemical composition and toxicity and/or safety of herbal extracts from the medicinal plants that are commonly used to manage asthma in Malawi. This was achieved through qualitative and quantitative assessment of flavonoids and phenolics, screening for antioxidant activity using 1, 1-diphenyl-2-picryl-hydrazyl (DPPH) assay and Ferric reducing antioxidant power assay (FRAP) as well as validated in vitro and in vivo acute toxicity test on Wistar rats of ethanolic herbal extracts of Erythrina abbysinica Lam. ex DC., Paederia bojeriana (A.Rich. ex DC.) Drake and Trichodesma zeylanicum (Burm.f.) R. Br. The results showed that Trichodesma zeylanicum (Burm.f.) R. Br, Paederia bojeriana (A.Rich. ex DC.) Drake and Erythrina abbysinica (Lam. ex DC) contained flavonoids and phenols. Highest total flavonoid content was found in E. abyssinica (Lam. ex DC.), (806.12±0.01 QE/mg). Highest total phenolic content was also found in E. abyssinica (Lam. ex DC.) (98.48±0.08 mg GAE/g). Antioxidant activity using DPPH % inhibition was highest in E. abyssinica (Lam. ex DC.) (86.59%) while FRAP results were highest in T. zeylanicum (Burm.f.) R. Br (21.85mg TAEC/g). In vitro toxicity showed that ethanolic root extract of P. bojeriana (A.Rich. ex DC.) Drake had the lowest LC50 values (LC50 = 11.09μg/ml) however, in vivo toxicity studies showed LC50 of 2000mg/kg in all extracts. This study has revealed that the ethanolic extracts of all extracts are rich in phytochemicals and antioxidant activities that are indicative of asthmatic activity in human beings according to the literature. The study has also shown that the plants are toxic in vitro but non-toxic in vitro.